ARCHOSAUROMORPH REMAINS FROM THE TARJADOS FORMATION (EARLY–MIDDLE TRIASSIC, NW ARGENTINA) (Ameghiniana, 2015)
The Agua de la Peña Group of the Ischigualasto-Villa Unión Basin (northwestern Argentina) documents the evolution of archosauromorph assemblages in western Gondwana during the late Middle and Late Triassic. However, the South American archosauromorph record in the aftermath of the Permo/Triassic mass extinction (Early–early Middle Triassic) is remarkably scarce and restricted to isolated bones. Here, we describe a recently collected isolated second sacral vertebra and rib that represents one of the few fossils known from the Lower–Middle Triassic Tarjados Formation, the unit that underlies the Agua de la Peña Group. This specimen is identified as an archosauromorph because of the presence of a non-notochordal vertebra and a bifurcated distal end of the second sacral rib. A quantitative phylogenetic analysis places the new specimen as an archosauromorph more derived than protorosaurs. In particular, this specimen resembles Pamelaria, Prolacerta and early rhynchosaurs in the presence of a squared posterior projection of the bifurcated second sacral rib. The new specimen represents the first body fossil of a diapsid formally described in the Tarjados Formation and the oldest member of the group in the Ischigualasto-Villa Unión Basin. As a result, this specimen increases the high-level taxonomic richness of Archosauromorpha in South America in the aftermath of the Permo/ Triassic mass extinction. Resumen. RESTOS DE UN ARCOSAUROMORFO DE LA FORMACIÓN TARJADOS (TRIÁSICO TEMPRANO–MEDIO, NO ARGENTINA). El Grupo Agua de la Peña de la Cuenca de Ischigualasto-Villa Unión (noroeste de Argentina) documenta la evolución de las faunas de arcosauromorfos en el oeste de Gondwana durante el Triásico Medio tardío y Triásico Tardío. Sin embargo, el registro de arcosauromorfos sudamericanos luego de la extinción masiva permo/triásica (Triásico Temprano–Medio temprano) es particularmente escaso y restringido a huesos aislados. Describimos aquí una vértebra y costilla sacra colectada recientemente, que representa uno de los pocos fósiles conocidos de la Formación Tarjados (Triásico Inferior–Medio), unidad que subyace al grupo Agua de la Peña. Este espécimen es identificado como un arcosauromorfo debido a la presencia de una vertebra no notocordal y un extremo distal birfurcado de la segunda costilla sacra. Un análisis filogenético cuantitativo ubica al nuevo espécimen como un arcosauromorfo más derivado que los protorosaurios. En particular, este ejemplar se asemeja a Pamelaria, Prolacerta y rincosaurios basales en la presencia de una proyección posterior cuadrangular del extremo distal de la segunda costilla sacra. El nuevo espécimen representa el primer registro fósil corpóreo formalmente descripto de un diápsido en la Formación Tarjados y el más antiguo para el grupo en la Cuenca de Ischigualasto-Villa Unión. Como resultado, este ejemplar incrementa la riqueza taxonómica de Archosauromorpha en América del Sur inmediatamente después de la extinción masiva Permo/Triásica.